KESADARAN LINGKUNGAN PETERNAK DALAM MENGELOLA DAMPAK USAHA TERNAK - Wijaya, Thaufan Hidayatullah Surya; Sriyono, Sriyono (Tahta Media Group, 2024)
This study aims to analyze the level of environmental awareness among livestock farmers and the factors influencing their behavior in managing the environmental impacts of livestock activities in Tegalgondo Village, Wonosari, Klaten. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation, and analyzed using thematic analysis techniques. The findings indicate that farmers’ environmental awareness is at a moderate level, with adequate understanding of the impacts of livestock waste on environmental cleanliness and community comfort. However, waste management practices vary, ranging from traditional methods to the adoption of simple technologies such as composting and biogas utilization. Economic considerations and community social norms are identified as the dominant factors shaping environmental behavior, followed by environmental literacy, institutional support, and infrastructure availability. The study highlights the need for a holistic approach integrating continuous environmental education, economic incentives, and strengthened local institutions to promote environmentally friendly and sustainable livestock systems.